EMPOWERING MATHEMATICAL PROFICIENCY BY DEVELOPING ENRICHMENT BOOK IN THE TOPIC OF RATIONAL NUMBERS - Etika Ramadani; Sukardi Sukardi (Aksioma: Jurnal Program Studi Pendidikan Matematika, 2024)
In Indonesia, there exists a significant gap in mathematical proficiency levels among students, evidenced by declining achievement rates over time and exacerbated by the COVID-19 pandemic, as revealed by recent studies and assessments such as PISA 2022. This research aims to develop an enrichment book in the topic of rational numbers that can enhance the mathematical proficiency level of junior high school students. This research uses the R&D approach which adopts the ADDIE model. The research instruments used in this study include validation sheets for subject matter expert, validation sheets for graphic expert, response questionnaire for teacher, pretest sheets, and posttest sheets. After the initial draft of the enrichment book was produced, the research continued with validating the book by a subject matter expert, a graphic expert, and a mathematics teacher . In the implementation phase, the validated and revised book was then tested on 29 seventh-grade students at Al Falah Junior High School, located in Dago region, Bandung city. Descriptively, the average score of students' pretest was 32.6%, while the average score of their posttest was 75.2%. The enrichment book has been shown to improve students’ scores significantly according to the N-gain, meaning that it significantly enhances students' mathematical proficiency level. Based on the established categories, these results indicate that the developed enrichment book can enhance students' mathematical proficiency level.